Water Contamination, Sanitation Practices, and Public Health Risks: A Cross-Sectional Study - Ritika Karna; Susmita Ghale; Prachi Kumari; Neelesh Kumar Maurya (International Journal of Sustainability, 2026)
Contaminated water remains one of the biggest obstacles to public health, especially in developing countries, partly due to a lack of sanitation systems and lack of knowledge about the dangers. This paper describes the causes of water resource contamination and the ways in which they are transmitted, the lack of knowledge of the public, and what can be done to make it less of a problem, including a cross-sectional study of 31 people living in urban, semi-urban, and rural locations in India. The research shows that the main causes of waterborne diseases are living (bacteria, viruses, parasites) and non-living (heavy metals, industrial waste) and political water contaminants. 87.1% of the respondents are aware of untreated water as a transmitter of diseases, and 96.8% are aware of the health risks associated with irresponsible disposal of waste. Other serious gaps include a 50% waste separation practice and the aforementioned lack of water tank servicing. This study shows the need for systems that are combined with the strategy. The research shows wide acceptance of the need for WASH (Water, Sanitation, and Hygiene) programs as a strategy for improving the health of the public. Combined with a strategy for improving the health of the public, this study shows the wide acceptance of the need for WASH (Water, Sanitation, and Hygiene) programs as a strategy for improving the health of the public.
Keywords: Community road; contaminated water and water management; government policy implementation; water safe integrated management